Fractionnement Géochimique Des Eléments Traces Métalliques (Etm) Dans Les Sédiments Du Delta De L’ouémé Au Bénin - Rodrigue A.M.A. Adechina; Nelly C. Kelome; Waris Chouti; Jéchonias B. Hounkpe; Nambinina R. F. Randriana (European Scientific Journal, ESJ, 2018)
Due to the inherent damages of trace elements to living organisms, the amount of bio available metal is considered to be a quantity that conditions the becoming of aquatic ecosystems. The aim of this work is to evaluate the proportion of Pb, Cu and Cd that are biologically available in the superficial sediments of the Ouémé estuary as well as the influence of environmental factors on the becoming of these metals. Fractionation of the metals was performed according to the sequential extraction method and their measurement was done by inductively coupled plasma mass spectrometer (ICP-MS). Physicochemical parameters evaluated are: granulometry, pH, cation exchange capacity (CEC), organic carbon (Corg), iron, aluminum and calcium oxides (Fe2O3, Al2O3 and CaO). Risk indices related to metal fractionation were evaluated followed by statistical processing in R 3.3.2. It appears that: 39.44% of the Cd are preferentially bound to the exchangeable fraction, 37.25% of the Pb are for the reducible fraction and 47.47% of the Cu for the oxidizable fraction. Risk levels are in the low to very high range. The richness of materials is revealed as a factor limiting the bioavailability of metals while CaO facilitates the bioavailability in high risk sites. Liquid and solid wastes from the Dantokpa market are the potential sources of metals.